Improvement of turkish delight production technology using a developed multi-component fruit and vegetable paste - Kasabova, Kateryna; Касабова, Катерина Рубенівна; Samokhvalova, Olga; Самохвалова, Ольга Володимирівна; Zagorulko, Aleksey; Загорулько, Олексій Євгенович; Zahorulko, Andrii; Загорулько, Андрій Миколайович; Babaiev, Serhii; Бабаєв, Сергій Олександрович; Bereza, Olena; Береза, Олена Юріївна; et al. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР", 2022)
The object of this study is the technology of Turkish delight production based on fruit and vegetable paste with a high content of physiologically functional ingredients. The chemical composition of Turkish delight has been optimized by introducing physiologically functional ingredients. As a source of physiologically functional ingredients, it was proposed to use a multicomponent fruit and vegetable paste from apples, quince, pumpkins, made in an improved way. The technique is characterized by concentrating the paste in the rotary evaporator for 30...42 s at a temperature of 60...63 °C under conditions of preheating the purée to 50...52 °C. The dependence of the effective viscosity on the shear rate of samples of fruit and vegetable pastes was determined and it was found that the best indicators characterized the paste with a formulation ratio of raw materials: apple – 30 %; quince – 50 %; pumpkin – 20 %. The resulting paste has good organoleptic properties and a high content of dietary fiber, ascorbic acid, polyphenolic compounds.It has been established that the production of Turkish delight with the addition of the developed fruit and vegetable paste provides the product with good organoleptic characteristics. Namely, it is characterized by a sweet-sour taste with a pleasant smell of quince, rich yellow-orange color, gelatinous, slightly viscous consistency, and the proper shape with a clear contour. Also, the addition of fruit and vegetable paste reduces the formulation amount of starch by 20 % while the resulting Turkish delight is characterized by a high strength value τ=38 kPa. The improved technology of Turkish delight could expand the range of "healthy products" with increased nutritional value. In addition, the proposed technique and the modes of concentration make it possible to organize the process of paste production using energy-saving equipment Об’єктом дослідження є технологія виробництва лукуму на основі плодоовочевої пасти з високим вмістом фізіологічно функціональних інгредієнтів. Хімічний склад лукум-лукуму оптимізовано шляхом введення фізіологічно функціональних інгредієнтів. В якості джерела фізіологічно функціональних інгредієнтів запропоновано використовувати багатокомпонентну фруктово-овочеву пасту з яблук, айви, гарбуза, виготовлену удосконаленим способом. Спосіб характеризується згущенням пасти в роторному випарному апараті протягом 30...42 с при температурі 60...63 °С в умовах попереднього підігріву пюре до 50...52 °С. Визначено залежність ефективної в’язкості від швидкості зсуву зразків плодоовочевої пасти та встановлено, що найкращими показниками характеризується паста з рецептурним співвідношенням сировини: яблуко – 30 %; айва – 50 %; гарбуз – 20 %. Отримана паста має добрі органолептичні властивості та високий вміст харчових волокон, аскорбінової кислоти, поліфенольних сполук. Встановлено, що виробництво лукум-лукуму з додаванням розробленої плодоовочевої пасти забезпечує продукту добрі органолептичні показники. А саме характеризується кисло-солодким смаком з приємним запахом айви, насиченим жовто-оранжевим кольором, драглистою, злегка в’язкою консистенцією, правильною формою з чітким контуром. Також додавання фруктово-овочевої пасти зменшує кількість крохмалю в рецептурі на 20 %, а отриманий лукум характеризується високим показником міцності τ=38 кПа. Удосконалена технологія лукум-лукуму могла розширити асортимент «здорових продуктів» з підвищеною харчовою цінністю. Крім того, запропонована техніка та режими збагачення дають можливість організувати процес виробництва пасти з використанням енергозберігаючого обладнання.
Удосконалення технології лукуму з використанням розробленої багатокомпонентної плодовоовочевої пасти
Keywords: Turkish delight; лукум; fruit and vegetable paste; фруктово-овочева паста; structural and mechanical properties; структурно-механічні властивості; physiologically functional ingredients; фізіологічно-функціональні інгредієнти; quality indicators; показники якості